Environmental Change in South-East Asia - Bryant, Raymond; Parnwell, Michael (Taylor & Francis, 1997)
Environmental Change in South-East Asia brings together scholars, journalists, consultants and NGO activists to explore the interaction of people, politics and ecology. Ostensibly "green" activities - plantation forestry, eco-tourism, hydro-electricity - are revealed as guises used by elites to promote their own political and economic interests. Highlighting fatal flaws in presently exclusive economic and ecological approaches, the authors stress that neither the quest for sustainable development nor the process of environmental change itself can be understood without reference to political processes.